Measuring management practices in primary health care facilities – development and validation of management practices scorecard in Nigeria - Mabuchi, Shunsuke (Glob Health Action, 2020)
BACKGROUND: In low- and middle-income countries, there is scarcity of validated and reliable measurement tools for health facility management, and many interventions to improve primary health care (PHC) facilities are designed without adequate evidence base on what management practices are critical. OBJECTIVE: This article developed and validated a scorecard to measure management practices at primary health care facilities under the performance-based financing (PBF) scheme in Nigeria. METHODS: Relevant management practice domains and indicators for PHC facilities were determined based on literature review and a prior qualitative study conducted in Nigeria. The domains and indicators were tested for face validity via experts review and organized into an interviewer-administered scorecard. A stratified random sampling of PHC facilities in three States in Nigeria was conducted to assess the reliability and construct validity of the scorecard. Inter-rater reliability using inter-class correlation (ICC) (1, k) was assessed with one-way ANOVA. Exploratory factor analysis (EFA) was conducted to assess the construct validity, and an updated factor structure were developed. RESULTS: 32 indicators and 6 management practice domains were initially described. Ordinal responses were derived for each indicator. Data on the scorecard were obtained from 111 PHC facilities. The ICC of mean ratings for each team of judges was 0.94. The EFA identified 6 domains (Stakeholder engagement and communication; Community-level activities; Update of plan and target; Performance management; Staff attention to planning, target, and performance; and Drugs and financial management) and reduced the number of indicators to 17. The average communality of selected items was 0.45, and item per factor ratio was 17:6. CONCLUSIONS: Despite a few areas for further refinement, this paper presents a reliable and valid scorecard for measuring management practices in PHC facilities. The scorecard can be applied for routine supervisory visits to PHC facilities, and can help accumulate knowledge on facility management, how it affects performance, and how it may be strengthened.